A LA MEMORIA DEL DOCTOR DON PIO DEL RIOHORTEGA MIEMBRO HONORARIO DE LA ACADEMIA NATIONAL DE MEDICINA DE MEXICO - PERRIN, TOMAS G (Instituto Investigaciones Agrícolas, CD MEXICO, DF, MEX, 1946)
Brucellae can use the cytoplasm of a variety of cells as a source of material for growth In infected guinea pigs, Brucellae were found growing in large numbers in the cytoplasm of macrophages, fibroblasts, endothelial and reticular cells When such an in
BOL INST ESTUD MED BIOL
Keywords: DOCTOR, MIEMBRO, ACADEMIA NATIONAL DE MEDICINA, MEXICO; CIENCIAS MEDICAS; MEDICINA GENERAL